Enabling Agrifood Systems Transformation in South Asia with Data and Evidence: Opportunities and Challenges (Webinar session 10) - International Maize and Wheat Improvement Center (2024)
South Asia, home to one quarter of the global population, faces issues such as poverty, malnutrition, and unsustainable food production systems despite being a major producer of food. The region faces escalating levels of unhealthy food consumption, unsustainable farming practices, and the adverse impacts of climate change. TAFSSA (Transforming Agrifood Systems in South Asia), a CGIAR Regional Integrated Initiative, seeks to deliver actionable evidence and scalable innovations in Bangladesh, India, and Nepal.